2022
DOI: 10.3390/ijerph19148648
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Behaviors of Korean Golf Travelers Based on the Choice Attributes of Golf Courses in Southeast Asia

Abstract: The purpose of this study was to understand customer behavior among Korean golf travelers based on the choice attributes of golf courses in Southeast Asia. This study was based on Creswell and Clark’s triangulation design, a mixed-methods research framework that compares the results of quantitative and qualitative investigations. The results of the quantitative study were as follows. ‘H1. Golf course choice attributes will have a positive effect on customer satisfaction’ was partially accepted. Among choice at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We found that the availability and condition of golf club amenities play a pivotal role for these golfers, significantly impacting their overall experience and the club's revenue generation. At the same time, major amenities such as the golf course and clubhouse are indeed crucial (Cham et al ., 2021; Lee and Lee, 2022; López-Bonilla et al ., 2019; Portugal et al ., 2020; Song et al ., 2021; Thanh et al ., 2021; Zhang et al ., 2022). As evidence, some golfers noted that lockers in Thailand and Indonesia were consistently well-maintained, aesthetically pleasing and smelled pleasant, factors that contributed to their overall positive impression and intention to return (Brown et al ., 2017; Brey and Meitner, 2022; Kang et al ., 2022; Kim, 2020; Kwon et al ., 2021).…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the availability and condition of golf club amenities play a pivotal role for these golfers, significantly impacting their overall experience and the club's revenue generation. At the same time, major amenities such as the golf course and clubhouse are indeed crucial (Cham et al ., 2021; Lee and Lee, 2022; López-Bonilla et al ., 2019; Portugal et al ., 2020; Song et al ., 2021; Thanh et al ., 2021; Zhang et al ., 2022). As evidence, some golfers noted that lockers in Thailand and Indonesia were consistently well-maintained, aesthetically pleasing and smelled pleasant, factors that contributed to their overall positive impression and intention to return (Brown et al ., 2017; Brey and Meitner, 2022; Kang et al ., 2022; Kim, 2020; Kwon et al ., 2021).…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…On the supplier side, Malaysia, Indonesia and Thailand offer a diverse golf tourism industry with strengths in championship-calibre courses, stunning natural landscapes and a well-developed infrastructure (Lee and Lee, 2022). They can provide high-quality golf facilities, a stable political environment and a multicultural appeal (Jeong, 2023).…”
Section: Golf Tourism Experience 125mentioning
confidence: 99%
See 2 more Smart Citations
“…Golf rapidly became popular in Korea in the 1990s, and the number of golf courses increased [ 7 ], and the number of people who play golf significantly increased. However, several obstacles prevented its popularization [ 8 ]. Green fees rose above the inflation rate over the years, holding back the popularization of golf due to travel time and accessibility issues with golf courses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%